Hypertriglyceridemia, Metabolic Syndrome, and Cardiovascular Disease in HIV-Infected Patients: Effects of Antiretroviral Therapy and Adipose Tissue Distribution - Jeroen P. H. van Wijk; Manuel Castro Cabezas (International Journal of Vascular Medicine)
The use of combination antiretroviral therapy (CART) in HIV-infected patients has resulted in a dramatic decline in AIDS-related mortality. However, mortality due to non-AIDS conditions, particularly cardiovascular disease (CVD) seems to increase in this population. CART has been associated with several metabolic risk factors, including insulin resistance, low HDL-cholesterol, hypertriglyceridemia and postprandial hyperlipidemia. In addition, HIV itself, as well as specific antiretroviral agents, may further increase cardiovascular risk by interfering with endothelial function. As the HIV population is aging, CVD may become an increasingly growing health problem in the future. Therefore, early diagnosis and treatment of cardiovascular risk factors is warranted in this population. This paper reviews the contribution of both, HIV infection and CART, to insulin resistance, postprandial hyperlipidemia and cardiovascular risk in HIV-infected patients. Strategies to reduce cardiovascular risk are also discussed.